Microbial community composition of Arctic cryoconite holes - Höscheler, Lara Marie (Jihočeská univerzita, 2023)
Cryoconite holes on glaciers are small holes filled with water, and microorganisms, and they are important habitats found on the surface of many glaciers worldwide. However, little research has been conducted on how cryoconite holes in close proximity and distributed over the same glacier differ in their microbial composition. This thesis focuses on the microbial composition of Arctic cryoconite holes from Svalbard glaciers situated in close proximity. A particular focus is placed on the comparison of their composition to already existing literature.
Microbial community composition of Arctic cryoconite holes
Keywords: Arctic cryoconite holes; 16S rRNA gene; microbial composition; Svalbard; taxonomic composition; Arctic cryoconite holes; 16S rRNA gene; microbial composition; Svalbard; taxonomic composition